PERTUMBUHAN DAN PRODUKSI PAPRIKA PADA BERBAGAI INTENSITAS RADIASI SURYA DI DATARAN RENDAH, BATAM(GROWTH AND PRODUCTION OF SWEET PEPPER CULTIVATED UNDER DIFFERENT SOLAR RADIATION INTENSITY AT LOWLAND REGION OF BATAM) - Z. Noor; B.F. Simatupang; Yonny Koesmaryono (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2005)
An experiment has been conducted in Batam Island to study the response of sweet pepper which cultivated at lowland of 20 m asl, during November 2001 to May 2002. Five varieties have been used namely, Bangkok, Gold Flame, New Zealand, Spartacus and Tropica. Plants cultivated using hydroponic system under plastic house with ultra violet protection. The radiation of 100% (control) and it reduce of 25% and 50% used as treatment in order to determine the microclimate favourable for growing pepper in lowland. The results shown that reducing radiation intensity has influenced significantly on vegetatif growth, except leaf area index. The plants were grown under 100% and 25% radiation intensity performed taller with more branches compare to the plants under 50%. Variety of Spartacus has grew tallest than others. Stem diameter of control plants performed bigger than other plants, while reducing radiation intensity has no effect significantly to leaf area index. Experiment also revealed that reducing radiation intensity has significant effect on number and weight of peppers per plant, and thickness of flesh, compare to control. In general, Gold flame has produced best quality than others varieties although it has less number of fruits compare to Tropica.